Thermal desorption of dimethyl methylphosphonate from MoO3. (3rd April 2017) - Head, Ashley R.; Tang, Xin; Hicks, Zachary; Wang, Linjie; Bleuel, Hannes; Holdren, Scott; Trotochaud, Lena; Yu, Yi; Kyhl, Line; Karslıoǧlu, Osman; Fears, Kenan; Owrutsky, Jeffrey; et al.
Abstract: Organophosphonates are used as chemical warfare agents, pesticides, and corrosion inhibitors. New materials for the sorption, detection, and decomposition of these compounds are urgently needed. To facilitate materials and application innovation, a better understanding of the interactions between organophosphonates and surfaces is required. To this end, we have used diffuse reflectance infrared Fourier transform spectroscopy to investigate the adsorption geometry of dimethyl methylphosphonate (DMMP) on MoO3, a material used in chemical warfare agent filtration devices. We further applied ambient pressure X-ray photoelectron spectroscopy and temperature programmed desorption to study the adsorption and desorption of DMMP. While DMMP adsorbs intact on MoO3, desorption depends on coverage and partial pressure. At low coverages under UHV conditions, the intact adsorption is reversible. Decomposition occurs with higher coverages, as evidenced by PCHx and POx decomposition products on the MoO3 surface. Heating under mTorr partial pressures of DMMP results in product accumulation. Abstract :